The study of service dogs for veterans with Post-Traumatic Stress Disorder: a scoping literature review - Emmy A. E. van Houtert; Nienke Endenburg; Joris J. Wijnker; Bas Rodenburg; Eric Vermetten (European Journal of Psychotraumatology, 2018)
The therapeutic application of human–animal interaction has gained interest recently. One form this interest takes is the use of service dogs as complementary treatment for veterans with Post-Traumatic Stress Disorder (PTSD). Many reports on the positive effect of PTSD Service Dogs (PSDs) on veterans exist, though most are indirect, anecdotal, or based on self-perceived welfare by veterans. They therefore only give a partial insight into PSD effect. To gain a more complete understanding of whether PSDs can be considered an effective complementary treatment for PTSD, a scoping literature review was performed on available studies of PSDs. The key search words were ‘dog’, ’canine’, ‘veteran’, and ‘PTSD’. This yielded 126 articles, of which 19 matched the inclusion criteria (six empirical studies). Recurrent themes in included articles were identified for discussion of methodology and/or results. It was found that results from most included studies were either applicable to human–animal interaction in general or other types of service animals. They therefore did not represent PSDs specifically. Studies which did discuss PSDs specifically only studied welfare experience in veterans, but used different methodologies. This lead us to conclude there is currently no undisputed empirical evidence that PSDs are an effective complementary treatment for veterans with PTSD other than reports on positive welfare experience. Additionally, the lack of development standardization and knowledge regarding welfare of PSDs creates risks for both human and animal welfare. It is therefore recommended that a study on the effect of PSDs be expanded to include evaluation methods besides self-perceived welfare of assisted humans. Future studies could include evaluations regarding human stress response and functioning, ideally conducted according to validated scientific methodologies using objective measurement techniques to identify the added value and mechanisms of using PSDs to assist treatment of PTSD in humans.